Security by any other name : negative security, positive security, and a multi-actor security approach - Hoggensen Gjørv, Gunhild (2012)
Examines the challenges and contradictions between some of the leading conceptions of security within the field of International Relations (IR), from those stating that the concept can only be employed by the state with regard to immediate, existential threats; to those that see security as the foundation of social life or as a human good.